2020
DOI: 10.1186/s13059-020-02205-x
|View full text |Cite
|
Sign up to set email alerts
|

Human A-to-I RNA editing SNP loci are enriched in GWAS signals for autoimmune diseases and under balancing selection

Abstract: Background Adenosine-to-inosine (A-to-I) RNA editing plays important roles in diversifying the transcriptome and preventing MDA5 sensing of endogenous dsRNA as nonself. To date, few studies have investigated the population genomic signatures of A-to-I editing due to the lack of editing sites overlapping with SNPs. Results In this study, we applied a pipeline to robustly identify SNP editing sites from population transcriptomic data and combined fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 57 publications
1
8
0
1
Order By: Relevance
“…SPAG6-ES might have a different function from SPAG6-FL. Here we found that SPAG6-ES inhibited the proliferation of porcine Sertoli cells and increased the apoptosis of cells, which is consistent with the results in Spag6-deficient mouse embryonic fibroblasts and SPAG6 silencing of SKM-1 cells (Zhang, Fu, et al, 2020;Zhang, Luo, et al, 2020;Zhang, Zhu, et al, 2020). SPAG6 promotes cell proliferation and inhibits apoptosis in Burkitt lymphoma cells (Zhang, Fu, et al, 2020;Zhang, Luo, et al, 2020;Zhang, Zhu, et al, 2020), which is in accordance with SPAG6-FL functions in porcine Sertoli cells.…”
Section: Discussionsupporting
confidence: 90%
“…SPAG6-ES might have a different function from SPAG6-FL. Here we found that SPAG6-ES inhibited the proliferation of porcine Sertoli cells and increased the apoptosis of cells, which is consistent with the results in Spag6-deficient mouse embryonic fibroblasts and SPAG6 silencing of SKM-1 cells (Zhang, Fu, et al, 2020;Zhang, Luo, et al, 2020;Zhang, Zhu, et al, 2020). SPAG6 promotes cell proliferation and inhibits apoptosis in Burkitt lymphoma cells (Zhang, Fu, et al, 2020;Zhang, Luo, et al, 2020;Zhang, Zhu, et al, 2020), which is in accordance with SPAG6-FL functions in porcine Sertoli cells.…”
Section: Discussionsupporting
confidence: 90%
“…RNA editing events have been reported to suffer under selection pressure. Zhang Rui’s team has found that RNA-edited SNP sites are highly enriched near autoimmune disease-related sites represented by Crohn’s disease, asthma, and allergic dermatitis and are subject to balanced selection ( 40 ). Duan’s group has reported that there are a large number of non-synonymous RNA editing sites (Nonsyn) that change amino acids in Drosophila , which show adaptive signals and are subject to positive natural selection ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study introduced the role of the IL6R-STAT3-ADAR1 axis in the oncogenicity of multiple myeloma (47). It should be noted that enrichment of ADAR SNP loci was identified in GWAS signals for autoimmune diseases (48). Corresponding to the evidence from the rna-seq dataset, rs12059682 C>T mutation could lead to a lower level of ADAR in the lymphocyte and fibroblast.…”
Section: Discussionmentioning
confidence: 99%